2017
DOI: 10.1016/j.kjms.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renin‐angiotensin system inhibitors on survival in kidney transplant recipients: A systematic review and meta‐analysis

Abstract: Renin-angiotensin system inhibitors, specifically angiotensin II converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB), have confirmed renoprotective benefits in patients with proteinuria and hypertension. However, it remains controversial whether these agents are beneficial to kidney recipients. We conducted this meta-analysis to evaluate the effects of ACEI/ARB treatment on patient and allograft survival after kidney transplant. The PubMed, Embase and Cochrane Library databases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…ACEIs and ARBs can lead to regression of LVH in kidney transplant recipients (187,188), but these same studies did not demonstrate an improvement in all-cause mortality (189). A recent systematic review and meta-analysis demonstrated a survival benefit with ACEI or ARB therapy in kidney transplant recipients but only from pooled cohort studies and not RCTs (190).…”
Section: Angiotensin-converting Enzyme Inhibitors (Acei) and Angiotenmentioning
confidence: 97%
“…ACEIs and ARBs can lead to regression of LVH in kidney transplant recipients (187,188), but these same studies did not demonstrate an improvement in all-cause mortality (189). A recent systematic review and meta-analysis demonstrated a survival benefit with ACEI or ARB therapy in kidney transplant recipients but only from pooled cohort studies and not RCTs (190).…”
Section: Angiotensin-converting Enzyme Inhibitors (Acei) and Angiotenmentioning
confidence: 97%